VD_FINDINFO HC / 2011 / 344 vom 7. Juni 2011 - VD Tribunal cantonal (2011)
SOMMATION, SUSPENSION DE LA PRESTATION D'ASSURANCE, COMPÉTENCE RATIONE MATERIAE | 86 al. 1 CO, 86 al. 2 CO, 87 al. 1 CO, 87 al. 2 CO, 20 al. 1 LCA, 20 al. 3 LCA, 21 al. 2 LCA, 236 CPC (CH), 237 CPC (CH), 308 al. 1 let. a CPC (CH)